Genetic data and radiocarbon dating question Plovers Lake as a Middle Stone Age hominin-bearing site. Issue 131 (June 2019) - Lombard, Marlize; Malmström, Helena; Schlebusch, Carina; Svensson, Emma M.; Günther, Torsten; Munters, Arielle R.; Coutinho, Alexandra; Edlund, Hanna; Zipfel, Bernhard; Jakobsson, Mattias
Abstract: We have sampled five out of the eleven previously identified human specimens and some faunal remains from the Plovers Lake site in the Cradle of Humankind, South Africa, for ancient DNA. We were successful in obtaining positive results for three of the human individuals and three 'buffalo' teeth. Based on ages obtained for flowstone and one bovid tooth, the site was interpreted previously as a hominin-bearing Middle Stone Age site of more than 60 000 years old. Our work, however, revealed that not all the material accumulated during the Pleistocene. Instead, the sampled humans and bovids most likely represent a Bantu-speaking Iron Age population (mtDNA haplogroup L3d) and their Nguni cattle. Newly obtained radiocarbon dates confirmed that these remains are probably no older than the last 500 years bp. This study demonstrates the usefulness of inter-disciplinary investigation into the human past, and the depositional and stratigraphic complexities that researchers in the Cradle of Humankind need to contend with before interpreting their assemblages.